Analisis Manajemen Risiko Pada Sistem Informasi Kurikulum Saraswati Menggunakan ISO 31000:2018 - Hutabarat, Marcella Anggreani Putri Maria; Suharyadi, S (STIKOM Tunas Bangsa Pematangsiantar, 2025)
Web SIKUSA has handled various web-based information systems with its 9 main pillars of service. There are various possibilities of risks, but SMK Saraswati has never analyzed the risks. This research aims to analyze risk management in the use of SIKUSA web. The focus of this research is a qualitative approach that uses the ISO 31000:2018 method. In the research, researchers found 19 possible risks, consisting of 13 possible risks with medium risk level and at low/low level there are 6 possible risks. Therefore, in the research conducted, a conclusion was obtained that in this regard there is no risk that is likely to endanger or potentially have an unfavorable impact on SMK Saraswati on the use of the SIKUSA web. Although there is a medium level risk, the risk can be overcome if there are recommended technical risk handling actions. For risk handling, it is recommended to conduct structured handling through gradual maintenance, as well as additional supporting activities in the form of socialization or training for employees. SMK Saraswati is expected to always be vigilant and prepared for any risks that will arise by conducting proper risk management and risk handling